Musculocutaneous Latissimus Dorsi Phalloplasty - Bencic, Marko; Stojanovic, Borko; Bizic, Marta; Djordjevic, Miroslav L. (Indian Journal of Plastic Surgery, 2022)
The treatment of gender dysphoria consists of psychiatric evaluation, initiation of hormonal therapy, and the final step in an individual's transition, performing gender-affirming surgery. Construction of the neophallus is one of the most demanding tasks in genital affirming surgery of transgender men. The main objectives of phalloplasty are to achieve a cosmetically acceptable and functional phallus, with a neourethra that allows voiding in standing position, sufficient length and strength for possible penetrative intercourse, preserved tactile and orgasmic sensation, and acceptable donor site morbidity. The musculocutaneous latissimus dorsi flap has reliable and suitable anatomy (good size, volume, and length of neurovascular pedicle) to meet the esthetic and functional requirements of neophallus reconstruction. Despite many advantages, the main disadvantage of this flap is the lack of sensitivity. Although the radial free forearm flap technique is the most commonly performed procedure, musculus latissimus dorsi flap is an acceptable choice in gender-affirming surgery.
Keywords: transman; phalloplasty; latissimus dorsi flap; urethroplasty